Covid -19 Sebagai Alasan Pemutusan Hubungan Kerja - Jihan Ainun Mardian Septyawati; Merry Tjoanda; Sarah Selfina Kuahaty (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The Covid-19 pandemic is a non-natural disaster event that makes termination of employment due to force majeure (force majuere) carried out by the company or work payments to workers / workers, which in this case refers to law number 13 of 2003 concerning manpower and law number 11 of 2020 concerning job creation and includes presidential decree number 12 of 2020 which stipulates covid 19 as a non-natural disasterPurposes of the Research: The purpose of this study is to discuss Covid-19 as the reason for termination to find out as a reason for termination of employment where in carrying out termination of employment must perform obligations to fulfill the rights and obligations of workers.Methods of the Research: This research is a normative judicial research, the type of research is descriptive analysis through this research collecting data through primary and secondary legal materials then systematically to obtain conclusions or problems.Results of the Research: Termination of employment can be carried out by the company or employer due to the Covid-19 pandemic as a force majuere against / laborer, layoffs carried out based on the reasons of force majuere affect the company's obligation to fulfill the rights and obligations of the parties in the work agreement that has been mutually agreed upon, but also the rights and obligations that have been stipulated in various laws and regulations in the field of Manpower, the basis of the general provisions regarding force majeure (force majuere) is regulated in the provisions of articles 1244 and 1245 of the Civil Code